2015
DOI: 10.1111/cas.12675
|View full text |Cite
|
Sign up to set email alerts
|

Open‐label, randomized, comparative, phase III study on effects of reducing steroid use in combination with Palonosetron

Abstract: The purpose of this study is to compare the efficacy of a single administration of dexamethasone (DEX) on day 1 against DEX administration on days 1–3 in combination with palonosetron (PALO), a second-generation 5-HT3 receptor antagonist, for chemotherapy-induced nausea and vomiting (CINV) in non-anthracycline and cyclophosphamide (AC) moderately-emetogenic chemotherapy (MEC). This phase III trial was conducted with a multi-center, randomized, open-label, non-inferiority design. Patients who received non-AC ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 13 publications
0
44
0
1
Order By: Relevance
“…Aapro et al reported that a dexamethasone‐sparing regimen consisting of palonosetron plus single‐dose dexamethasone (d1 arm) would not be inferior to the same regimen followed by additional dexamethasone doses on days 2 to 3 after chemotherapy initiation (d3 arm) regarding complete response (CR; no emesis and no rescue medication) rate. Two subsequent randomized phase III studies were performed with a similar objective, which also showed the noninferiority of the dexamethasone d1 arm for the prevention of CINV in patients undergoing a broad range of MEC regimens . However, because of a wide range of noninferiority margin (15%) and limited number of subjects in these three studies, evidence for the noninferiority of the dexamethasone d1 arm in patients with risk factors for CINV is insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aapro et al reported that a dexamethasone‐sparing regimen consisting of palonosetron plus single‐dose dexamethasone (d1 arm) would not be inferior to the same regimen followed by additional dexamethasone doses on days 2 to 3 after chemotherapy initiation (d3 arm) regarding complete response (CR; no emesis and no rescue medication) rate. Two subsequent randomized phase III studies were performed with a similar objective, which also showed the noninferiority of the dexamethasone d1 arm for the prevention of CINV in patients undergoing a broad range of MEC regimens . However, because of a wide range of noninferiority margin (15%) and limited number of subjects in these three studies, evidence for the noninferiority of the dexamethasone d1 arm in patients with risk factors for CINV is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of a wide range of noninferiority margin (15%) and limited number of subjects in these three studies, evidence for the noninferiority of the dexamethasone d1 arm in patients with risk factors for CINV is insufficient. In addition, it is unclear whether well‐known risk factors for CINV, such as female sex, younger age, and history of alcohol consumption , modify the treatment effect on the antiemetic outcome .…”
Section: Introductionmentioning
confidence: 99%
“…45 This study administered palonosetron 0.75 mg, which is the commonly used dose in Japan. Netupitant-palonosetron is a netupitant (an NK-1 antagonist) plus palonosetron combination that has recently been included in the NCCN guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…2011 ASCO guidelines recommended use of a two-drug combination of palonosetron (day 1 only) and dexamethasone (days 1-3) in patients receiving MEC; when palonosetron is not available, it may be substituted with a first-generation 5-HT 3 serotonin receptor antagonist, preferably granisetron or ondansetron [1]. Several randomized studies, however, showed that a regimen of palonosetron and single-day dexamethasone is noninferior to palonosetron plus dexamethasone for 2 or 3 days in controlling CINV induced by MEC chemotherapy [15][16][17]. These findings are reflected in the recommendations of the MASCC/ESMO Antiemetic Guideline 2016 [18]: for the prevention of acute nausea and vomiting in MECtreated patients, a 5-HT 3 receptor antagonist plus dexamethasone on day 1 is recommended, while the use of dexamethasone on days 2 and 3 can be considered in patients receiving MEC with well-known potential for delayed nausea and vomiting (such as oxaliplatin, anthracycline or cyclophosphamide).…”
Section: Clinical Evaluation Of Granisetron Transdermal Delivery Systemmentioning
confidence: 99%